COMPARATIVE STUDY OF CHARACTER EDUCATION MODEL IN UNY INDONESIA AND PUNJABI UNIVERSITY INDIA - Aman Aman; Balraj Singh (Universitas Negeri Yogyakarta, 2022)
The purpose of this research is to find out: 1) comparison of character education model in Yogyakarta State University Indonesia and Punjabi University Patiala India, 2) effectiveness of character education model at Yogyakarta State University Indonesia and Punjabi University Patiala India. The method of this research was qualitative research and used comparative study design approach. The most appropriate strategy of this research was embedded research (stuck research) because the research has been planned in detail in the proposal before the researchers plunged into the field. The steps used were: 1) collecting source through multi-technique); 2) reducing data in order to simplify and categorizing data; 3) presenting data in the form of qualitative description; 4) drawing conclusions and 5) preparing research reports, and formulating recommendations comparison research results. The aims of this research are: plotting the comparison of character education model in Yogyakarta State University Indonesia and Punjabi University Patiala India, as well as obtaining information about effectiveness model of character education at Yogyakarta State University and Punjabi University Patiala, India. Having comparable Character education model in Yogyakarta State University Indonesia with Punjabi University India, then further prepared a good recommendation for Yogyakarta State University and Punjabi University Patiala India about the effective model of character education in college.